PRODUKSI TEPUNG UBI KAYU BERPROTEIN: KAJIAN PEMANFAATAN TEPUNG KACANG BENGUK SEBAGAI SUMBER NITROGEN RAGI TEMPE - Marniza, Marniza; Medikasari, Medikasari; Nurlaili, Nurlaili (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
Cassava roots  have low protein content and short storage life. Fermentation of cassava using tempeh innoculum is one way to increase the protein content of cassava.  Cassava has low protein content therefore it  needs to add nitrogen for ragi tempeh  to grow. Velvet bean could be used to enrich  nitrogen source for the growth of tempeh mold in cassava fermentation. The objectives of this research was to determine the influence of addition of velvet bean flour iton cassava fermentation using ragi tempeh which  will increase protein content  of the cassava and meet  SNI standard.  The experimental design used was a Completely Group Randomized Design, single factor with six concentration level : 0%;  6%;  8%;  10%;  12%;  14% with three replications. Data was evaluated using Bartlett test, Tukey test and BNT 5%.  The high protein content 11,51%  was obtained from the addition of  velvet bean flour at concentration  of 12%. The mousture and HCN content in all treatments have meet the  SNI 01-2997-1992  standard for cassava flour, but not for  minerals and starch contents.